Encapsulation of Naproxen with Meso-Tetradodecyl-Pyrogallol[4]arene: Complexation, Characterization, and Molecular Docking Insights: Enkapsulasi Naproksen dengan Meso-Tetradodecyl-Pyrogallol[4]arene: Pembentukan Kompleks, Karakterisasi, dan Wawasan Docking Molekuler - Essam S. Khudhier; Maan S. AlNuaim; Khulood H. Oudah (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Supramolecular encapsulation using macrocyclic hosts has emerged as a strategy to address solubility and stability limitations of poorly water-soluble drugs. Specific Background: Naproxen, a widely prescribed nonsteroidal anti-inflammatory drug, exhibits low aqueous solubility and gastrointestinal irritation, prompting investigation of meso-tetradodecyl-pyrogallol[4]arene (C12-Py[4]arene) as a hydrophobic macrocyclic carrier capable of forming inclusion complexes through noncovalent interactions. Knowledge Gap: Although pyrogallol[4]arenes possess tunable cavities and self-assembly properties, detailed characterization of naproxen encapsulation combining spectroscopic, morphological, and molecular docking analyses remains limited. Aims: This study aimed to encapsulate naproxen within C12-Py[4]arene via mechanochemical grinding, characterize the resulting complex (PYX7), and evaluate binding affinity using molecular docking. Results: UV–Vis spectroscopy revealed bathochromic shifts at 318.00 and 332.50 nm, while FTIR analysis showed C=O band shifting from 1725 to 1689 cm⁻¹, confirming hydrogen bonding. SEM demonstrated altered semi-spherical agglomerates with heterogeneous morphology. Docking simulations predicted favorable binding energy (−7.00 kcal/mol), supported by hydrogen bonding and π–π stacking interactions within the hydrophobic cavity. Novelty: The integration of solvent-free complexation, spectroscopic validation, SEM imaging, and in silico modeling provides a comprehensive profile of PYX7 formation. Implications: These findings identify C12-Py[4]arene as a supramolecular carrier for naproxen and support further evaluation of pyrogallol[4]arene-based systems in NSAID delivery research. Keywords: Supramolecular Encapsulation, Naproxen, Pyrogallol4arene, Inclusion Complex, Molecular Docking Key Findings Highlights: Spectral shifts verified noncovalent host–guest interactions. Microscopy demonstrated nano-assembly formation with structural heterogeneity. Computational modeling showed favorable binding energetics and structural complementarity.